1997
DOI: 10.1037/1099-9809.3.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Missed, Dissed, and Pissed": Making Meaning of Neighborhood Risk, Fear and Anger Management in Urban Black Youth.

Abstract: The risk factor stress engagement, and coping experiences of African American youth are not well understood. Given the stressors of racism, hopeless perceptions of urban youth, and violence experience and exposure, anger experience and expression are reasonable resilient and risky reactions to this atmosphere of hostility. This study analyzed the impact upon the anger management of adolescents when calamity fears, neighborhood social capital, and kinship social support are known. The findings suggest that when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 39 publications
(38 reference statements)
5
87
1
Order By: Relevance
“…Thus, extended family members are intimately involved in the child-rearing and household activities in many African American families (Boyd-Franklin 1989;Franklin 1997). Kinship support is linked to better anger management in African American youth growing up in high risk neighborhoods (Stevenson 1997). In addition, kinship support has been found to lessen the association between negative contextual influences, including financial stress and maladaptive parenting practices, and youth internalizing and externalizing difficulties (Taylor 2010;Taylor et al 2014).…”
Section: Kinship Supportmentioning
confidence: 97%
“…Thus, extended family members are intimately involved in the child-rearing and household activities in many African American families (Boyd-Franklin 1989;Franklin 1997). Kinship support is linked to better anger management in African American youth growing up in high risk neighborhoods (Stevenson 1997). In addition, kinship support has been found to lessen the association between negative contextual influences, including financial stress and maladaptive parenting practices, and youth internalizing and externalizing difficulties (Taylor 2010;Taylor et al 2014).…”
Section: Kinship Supportmentioning
confidence: 97%
“…In one of the only studies of neighborhood connection, Witherspoon and Hughes (2005) found that feelings of connectedness are positively associated to grades after adjusting for structural neighborhood and perceived negative neighborhood characteristics. Furthermore, the literature suggests that neighborhood characteristics, such as perceived problems (Aneshensel & Sucoff, 1996;Seidman et al, 1998), residential mobility (Sampson et al, 1997), and pervasive fears associated with living in urban areas (Stevenson, 1997) are related to adolescent academic and psycho-social well-being and may be associated with lower levels of connectedness to the neighborhood (Witherspoon & Hughes, 2005), making it necessary to assess perceived negative neighborhood characteristics and residential mobility when examining neighborhood connection. It is also important to note that, similar to schools, neighborhoods afford youth opportunities to connect with peers.…”
Section: Connection To the Context: Neighborhoodmentioning
confidence: 99%
“…Some youth may be socialized to appear tough or unafraid in the face of real danger as a means of coping or survival. This tough stance may in turn support aggressive responses to perceived or actual threats to safety (e.g., Spencer et al 1995;Stevenson 1997). Both explicit and implicit messages from parents, such as those encouraging the use of aggression (e.g., "If someone hits you, you should hit them back") may also influence normative beliefs about aggression and aggressive behavior (e.g., Copeland-Linder et al 2007;Orpinas et al 1999;Solomon et al 2008).…”
mentioning
confidence: 96%